Market concentration in the Galician canned industry: Has it been consolidated through green innovation? - Raquel Fernández-González; Rosa María Ricoy-Casas; José María Lago Cabo (Discover Sustainability)
Abstract This study examines the canning industry in Galicia, a region in northwestern Spain, which is the most significant in Europe in terms of volume and value, and the second most important worldwide. Within both supranational and national institutional contexts, green innovation strategies have been established for the food industry. Recognizing the importance of the fish processing sector in Galicia, the regional government has implemented three successive strategic plans, emphasizing green innovation. These new regulations and the allocation of public funds have spurred innovative initiatives towards green practices. However, the adoption of green innovation is progressing at different rates, with large and medium-sized companies leading the way, while small and micro enterprises face more challenges. This research analyzes the evolution of the market structure of the Galician canning industry using various concentration and market stability indexes. The analysis considers the sector’s performance in light of strategies aimed at enhancing digitalization, supported by the relevant institutional framework. The findings indicate a slight variation in concentration indices, maintaining a consistent trend throughout the period analyzed. Despite the top four companies holding approximately 60% of the market share, the HHI index, which remains below 1500, suggests that the market is not highly concentrated. Clinical trial number: Not applicable.